The ASPP proteins complex and cooperate with p300 to modulate the transcriptional activity of p53 - Gillotin, S; Lu, X (2011)
Understanding how p53 is able to specifically respond to particular stress signals and regulate many different signalling pathways remains a challenge. Several studies have demonstrated that p53's interactions with different protein partners are essential for it to be able to coordinate specific responses. In particular, the apoptotic pathway is regulated by p53 in cooperation with the Apoptosis Stimulating Proteins of p53 (ASPP) proteins. In this study, we showed that the ASPP proteins are able to bind and cooperate with p300, a well defined co-factor of p53, to selectively regulate p53's transcriptional activity on promoters such as p53-inducible gene 3 but not on p21waf1. This is the first demonstration that the ASPPs can function together with p300 in regulating the transcriptional activity of p53. © 2011 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.